Reprogramming, Circular Reasoning and Self versus Non-self: One-Stop Shopping with RNA Editing - Savva, Yiannis A.; Rezaei, Ali; St. Laurent, Georges; Reenan, Robert A. (Frontiers in Genetics, 2016)
Transcription of genetic information from archival DNA into RNA molecule working copies is vital for proper cellular function and is highly accurate. In turn, RNAs serve structural, enzymatic, and regulatory roles, as well as being informational templates for the ribosomal translation of proteins. Following RNA synthesis, maturing of RNA molecules occurs through various RNA processing events. One component of the collection of processes involving RNA species, broadly defined as RNA metabolism, is the RNA editing pathway and is found in all animals. Acting specifically on RNA substrates with double-stranded character, RNA editing has been shown to regulate a plethora of genomic outputs, including gene recoding, RNA splicing, biogenesis and targeting actions of micro RNAs and small interfering RNAs, and global gene expression. Recent evidence suggests that RNA modifications mediated via RNA editing influence the biogenesis of circular RNAs and safeguard against aberrant innate immune responses generated to endogenous RNA sources. These novel roles have the potential to contribute new insights into molecular mechanisms underlying pathogenesis mediated by mishandling of double-stranded RNA. Here, we discuss recent advances in the field, which highlight novel roles associated with the RNA editing process and emphasize their importance during cellular RNA metabolism. In addition, we highlight the relevance of these newly discovered roles in the context of neurological disorders and the more general concept of innate recognition of self versus non-self.